Stomatin-like protein 2 of turbot Scopthalmus maximus: Gene cloning, expression profiling and immunoregulatory properties. (February 2016) - Chi, Heng; Hu, Yong-hua
Abstract: Stomatin-like protein 2 (SLP-2) is a novel and unusual member of the stomatin gene superfamily. In this study, we obtained a full-length SLP-2 (SmSLP-2) cDNA from turbot ( Scopthalmus maximus ) spleen cDNA library. The cDNA sequence of SmSLP-2 contains a 5′-UTR of 107 bp, an ORF of 1050 bp, and a 3′-UTR of 959 bp. The ORF encodes a putative protein of 349 residues, which has a calculated molecular mass of 38.7 kDa. The SmSLP-2 protein possesses a prohibitin-homology (PHB) domain (residues 40 to 198) and shares 72.4–87.6% overall sequence identity with that of the teleost species. The highest expression of SmSLP-2 mRNA was found in the skin, followed by the head kidney, gut, spleen, liver, heart, gill and muscle. Moreover, both viral and bacterial pathogen infection resulted in the up-regulation of SmSLP-2 mRNA in the turbot head kidney and spleen in vivo. Subcellular localization analysis indicated that the SmSLP-2 proteins are mainly located in the peripheral membrane of ZF4 cells. This study also demonstrated that SmSLP-2 modulates IL-2 expression via active NFκB signaling pathway, and is possibly involved in host immune defense against bacterial and viral pathogens. Highlights: A SLP-2 (SmSLP-2) gene in turbot ( Scopthalmus maximus ) was identified. Both viral and bacterial pathogen infection resulted in up-regulation of SmSLP-2 mRNA in head kidney and spleen. The major pool of SmSLP-2 is the peripheral membrane in ZF4 cells. SmSLP-2 modulates IL-2 expression via active NFκB signaling pathway.